Anion exchanger 2 is critical for CD8+ T cells to maintain pHi homeostasis and modulate immune responses. Issue 5 (11th March 2014) - Concepcion, Axel R.; Salas, January T.; Sarvide, Sarai; Sáez, Elena; Ferrer, Alex; López, María; Portu, Ainhoa; Banales, Jesús M.; Hervás‐Stubbs, Sandra; Oude Elferink, Ronald P. J.; Prieto, Jesús; Medina, Juan F.
<x xml:space="preserve">Abstract</x> Mitogenic stimulation of lymphocytes involves alkalinization of intracellular pH (pHi). Subsequent pHi regulation may involve HCO3− extrusion through Cl−/HCO3− exchangers and/or Na+‐HCO3− co‐transporters with acid‐loading capability. Abnormalities in these mechanisms could result in immune dysfunctions, as suggested by the CD8+ T‐cell expansion encountered in mice lacking Ae2 (a widely expressed acid loader with electroneutral and Na+‐independent Cl−/HCO3− anion‐exchange activity). Here we report that CD8+ T cells but not CD4+ T cells or other lymphocyte populations, are crucially dependent on Ae2 for pHi regulation. While total lymphocytes (including isolated CD4+ T cells) exhibit Ae1 expression and Na+‐HCO3− co‐transport with acidifying potential, CD8+ T cells lack these acid‐loading mechanisms. In Ae2‐KO mice, CD4+ but not CD8+ T cells upregulate these potential Ae2 surrogates. As a consequence, Ae2‐KO CD8+ T cells exhibit alkalinized pHi, and dramatically increase their pHi upon CD3 stimulation. Moreover, stimulated Ae2‐deficient CD8+ T cells show enhanced intracellular production of IL‐2 and membrane expression of its receptor IL‐2Rα, together with increased cell proliferation and activation. These findings demonstrate that CD8+ T cells are critically dependent on Ae2 for pHi homeostasis and tuning of cell proliferation and activation. Ae2 thus constitutes a novel target to modulate CD8+ T‐cell responses.